ANALISIS REALISASI ANGGARAN UNTUK MENILAI EFEKTIVITAS DAN EFISIENSI KINERJA PEMERINTAH DI DINAS PERTANIAN DAN PETERNAKAN PROVINSI SULAWESI UTARA - Waney, Cindy Kareima; Saerang, David P. E.; Alexander, Stanley W. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2018)
Good governance is an eminent issue in the management of government administration today. The implementation of local government  can not be separated from the use and utilization of budget and regional income. And every year it is always the local goverment preparing a budget plan or called regional income and expenditure budgets . The purpose of  this study analyzed the budget realization report to assess the effectineness and efficiency od government performance in aggriculture and livestock servive of North Sulawesi Province period 2012-2014. Data analysis method used is data analysis calculation of effectiveness and efficiency. Level or criteria of effectiveness of expenditure budget in agriculture and livestock service of North Sulawesi Province 2012-2014 vary for effevtive use the budget is quite effective in 2012 and 2013-2014 effective budget usage. So overall from 2012-2014, the level of effectiveness of agriculture and livestock expenditure budget of North Sulawesi Province experienced an effective increase. In the implementation of  agriculture and livestock expenditure budget  of the province of North Sulawesi in 2012-2014, already well processed and very efficient. Implementation of the 2012-2014 budget is categorized as very efficient because the efficiency level below 60%.Keywords : efficiency, effeectiveness, budget